Okoljska komunikacija političnih strank v obdobju parlamentarnih volitev v Sloveniji leta 2022 - Larisa Fabčič, Melanija (Komuniciranje okoljske krize, 2025)
Environmental protection has been an important issue in international political discourse since the late 1980s, but it only became more prominent in Slovenian politics in the first decade of the new century, when Slovenia joined the European Union in 2004, thereby committing itself to environmental protection and climate change mitigation. At the beginning of the second decade of the 21st century, the Covid 19 pandemic and the war in Ukraine significantly changed the political agenda, placing the issue of national security above and ahead of the fight against the environmental crisis. In the context of the 2022 parliamentary elections in Slovenia, this trend was very much in evidence. The issues of climate change, the environmental crisis and environmental protection featured in the election campaigns of some, but not all, parties. It is also striking that they were rarely directly addressed in the parties' TV and radio debates. This paper analyses how parties and the media communicated about the environmental crisis during the election campaign, based on party manifestos and TV debates.